Theoretical and Experimental Investigation of an Acetone-Filled Pulsating Heat Pipe Heat Exchanger for Waste Heat Recovery (Journal of Engineering, 2025)
In this work, a vertical pulsating heat pipe heat exchanger (PHPHE)  was designed for waste heat recovery, exchanging thermal energy between two air streams in a counterflow configuration. The heat exchanger consists of six rows, each row consists of one pulsating heat pipe (PHP), and each PHP has six turns. The working fluid used in the heat pipe was acetone with fill ratios of 50%, 60%, and 70%. The effect of evaporator inlet temperature at 40, 45, and 50°C and air velocity at 0.5, 0.7, and 0.9 m/s on the pulsating heat pipes consisting of three sections- evaporator, condenser, and adiabatic, whose dimensions were 25 x 25 x 10 cm, was studied. At the same time, the condenser temperature was maintained at 26°C. The system’s thermal resistance, effectiveness, and heat transfer were calculated using Engineering Equation Solver (EES) software. Results showed that the device's efficiency ranged from approximately 15% to 32%. The device performed better at a 50% fill ratio compared to other ratios, achieving high efficiency at low speeds.